PENERAPAN PROFIL PELAJAR PANCASILA DALAM PEMBELAJARAN IPAS DI SDN BETOKAN 2 DEMAK - Desyana Ajeng Safitri; Prasena Arisyanto; Filia Prima Artharina (STKIP Subang, 2023)
In the current era of modernization, the threat of losing national character is increasingly real. An incident that illustrates the weakening of education in forming a generation of character is crime involving students. Through science and science learning, we can create a Pancasila Student Profile that is in accordance with the national character. The focus of this research is how to apply the Pancasila Student Profile in science and science learning at SDN Betokan 2 Demak, and what are the supporting and inhibiting factors for implementing the Pancasila Student Profile in science and science learning at SDN Betokan 2 Demak. The aim of this research is to analyze the application of the Pancasila Student Profile in science and science learning at SDN Betokan 2 Demak, as well as to analyze the supporting and inhibiting factors for implementing the Pancasila Student Profile in science and science learning at SDN Betokan 2 Demak. This type of research is descriptive qualitative. Data collection methods through observation, interviews, questionnaires and documentation. The research setting was carried out at SDN Betokan 2 Demak. The research subjects were 4th grade students, school principals, and 4th grade teachers. The research results show that science and technology learning activities consist of 3 stages, namely the planning, implementation and evaluation stages. At each stage of these activities, the values ​​of the Pancasila Student Profile are realized, including having faith, being devoted to God Almighty, and having noble character, global diversity, working together, independently, reasoning critically and creatively. The obstacles that occur are the lack of understanding of educators regarding the profile of Pancasila students, limited school facilities and infrastructure, and the interactions of students outside of school. Meanwhile, the existing support includes the socialization of Pancasila student profiles for educators, school familiarization, and cooperation between teachers, school principals, parents, and other agencies related to education.